Postmortem genetic testing for cardiac ion channelopathies in stillbirths - Munroe,PB; Addison,S; Abrams,DJ; Sebire,NJ; Cartwright,J; Donaldson,I; Cohen,MM; Mein,C; Tinker,A; Harmer,SC; Aziz,Q; Terry,A; et al. (Circulation: Cardiovascular Genetics, 2018)
BackgroundAlthough stillbirth is a significant health problem worldwide, the definitive cause of death remains elusive in many cases, despite detailed autopsy. In this study of partly explained and unexplained stillbirths, we used next-generation sequencing to examine an extended panel of 35 candidate genes known to be associated with ion channel disorders and sudden cardiac death.Methods and ResultsWe examined tissue from 242 stillbirths (≥22 weeks), including those where no definite cause of death could be confirmed after a full autopsy. We obtained high-quality DNA from 70 cases, which were then sequenced for a custom panel of 35 genes, 12 for inherited long- and short-QT syndrome genes (LQT1-LQT12 and SQT1-3), and 23 additional candidate genes derived from genome-wide association studies. We examined the functional significance of a selected variant by patch-clamp electrophysiological recording. No predicted damaging variants were identified in KCNQ1 (LQT1) or KCNH2 (LQT2). A rare putative pathogenic variant was found in KCNJ2(LQT7) in 1 case, and several novel variants of uncertain significance were observed. The KCNJ2 variant (p. R40Q), when assessed by whole-cell patch clamp, affected the function of the channel. There was no significant evidence of enrichment of rare predicted damaging variants within any of the candidate genes.ConclusionsAlthough a causative link is unclear, 1 putative pathogenic and variants of uncertain significance variant resulting in cardiac channelopathies was identified in some cases of otherwise unexplained stillbirth, and these variants may have a role in fetal demise.